Teaching Australian Indigenous Studies: Non-Indigenous academics negotiating structural impediments in a regional context - Hook, Genine; Jessen, Nikki (The Australian Journal of Indigenous Education, 2022)
This paper examines the experiences of two non-Indigenous academics in a regional Australian university who taught/coordinated a first-year course, Introduction to Indigenous Australia (SCS130). Drawing on our own experiences, we explore the implications and contentious nature of non-Indigenous academics teaching Indigenous Studies and align this discussion with structural critique. As non-Indigenous academics, some argue that it is culturally disrespectful and pedagogically problematic for us to deliver this course. We consider that the work of embedding Indigenous perspectives should not be relegated solely the responsibility of Indigenous academics, and that our teaching contributes to reconciliation and begins to fill a significant gap in awareness and understanding among Australian students in higher education. The course SCS130 aims to introduce students to Indigenous perspectives through narratives, film, documentaries, academic and non-academic texts, biography and art. The objective of the course is to engage students with the complexity of colonisation and its ramifications for constructions of individual and national identities. Student survey qualitative data is used to provide an analysis of the course and to illustrate the conflict between our pedagogic practice, student expectations and the structural impediments to our decolonising teaching aims.